IKAN NAPOLEON (Cheilinus undulatus), SPESIES TERANCAM PUNAH DI KEPULAUAN NATUNA DAN ANAMBAS - Ayuningtyas Indrawati; Suparmo Suparmo (OSEANA, 2021)
Napoleon fish (Cheilinus undulatus) is one of the high value commodities in the live reef fish trade. The fishing pressure for this particular fish has threatened its population in the wild. The Napoleon fish was assessed as an endangered species in the IUCN Red List and listed on Appendix II of CITES (Convention on International Trade in Endangered Species). Indonesia is one of the largest exporters of the Napoleon fish, with the biggest source of exports from Natuna and Anambas Islands. The utilizations of Napoleon resources in Natuna and Anambas Islands include: (a) capturing juveniles from nature; (b) raising juveniles in capture-based aquaculture; and (c) exporting the Napoleon fish (Ranched-sourced) to Hong Kong as the main destination. The abundance of Napoleon fishes in the Natuna and Anambas Islands was very low. The management effort of Napoleon fisheries at the national level was regulated by implementing size limitation and export quota system for international trade to control the number of Napoleon fishes that can be exported annually. Further research is needed to find out the abundance, distribution, and biological aspects of juvenile Napoleon fishes in the Natuna and Anambas Islands. This information is required as a basis data for management recommendations to protect the Napoleon fish population in the wild.